Should we plan for contraction in health services? The Jamaican experience. - CUMPER, George E. (1993)
Notes that economic recession worldwide has been blamed for declining health care and health in developing countries. Suggests that the decline in Jamaica can be blamed equally on limitations of planning and management. Points out that existing planning procedures are associated with expansion, and do not work well in situations of contraction, nor does the existing health services management system provide impetus for contraction as it does for expansion.